The Testament of Stone: Understanding the past, present, and future cultural significance of the long lives of the Irish high crosses. - Dolan, Juliana (Ana) (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2024)
The Irish High Crosses are a unique group of monuments that, relative to their size, convey a exceptional amount of information about the early Christian period in which they were made. Over the past one hundred and fifty years, they have been the subject of a large body of scholarship, focused primarily on their insular art, iconography, chronology, and how they relate to crosses in the British Isles. However, very little attention has been paid to the untold stories of their long lives and their post-1200 survival. The physical fabric of the crosses is an unrecognised and undervalued source of evidence about their changing cultural significance during that time. In addition, the crosses that remain outdoors are vulnerable to climate change impacts but there is an absence of any public debate about their future. At present, there is no government policy for the protection of carved stone sculpture nor is there an inventory or condition audit for the crosses. This research attempts to address the gaps in our post 1200 understanding of the crosses by examining historical texts and images to advance knowledge of the changing cultural, political, and religious values that affected their survival. It reveals their post-Reformation role in the creation of Catholic and Protestant Irish identity which contributed to their survival and the retention of their cultural significance. In addition, ten case studies of high crosses are examined to determine what additional understanding can be achieved through a combination of a forensic analysis of their physical condition with their known biographies. The findings of the ten case studies, together with the historical evidence, are brought together to create a `Lexicon of Losses? which not only identifies shared patterns of loss in the past but also highlights their vulnerability to future climate change impacts. This thesis demonstrates that the histories of the crosses are far from static and this will continue to be the case into the future. It advocates for an acceptance of the crosses as a high-value and high-risk category of monument in order to provide clarity around the difficult question of maintaining their cultural significance in the face of climate change impacts. Finally, it aims to assist in addressing the role of official policy in maintaining their cultural significance into the future.
APPROVED
Keywords: High Cross; cultural significance; long lives